2001
DOI: 10.1161/01.cir.103.6.789
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Blockade Reverses Myocardial Fibrosis in a Transgenic Mouse Model of Human Hypertrophic Cardiomyopathy

Abstract: Background-Hypertrophic cardiomyopathy (HCM), the most common cause of sudden cardiac death in the young, is characterized by cardiac hypertrophy, myocyte disarray, and interstitial fibrosis. We propose that hypertrophy and fibrosis are secondary to the activation of trophic and mitotic factors and, thus, potentially reversible. We determined whether the blockade of angiotensin II, a known cardiotrophic factor, could reverse or attenuate interstitial fibrosis in a transgenic mouse model of human HCM. Methods a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
229
1
6

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(241 citation statements)
references
References 20 publications
5
229
1
6
Order By: Relevance
“…Recent data demonstrate that angiotensin II promotes cardiac fibrosis in part by activating Tgf-β signals (32). Moreover, the angiotensin II type I receptor antagonist losartan has had salutary effects on animal models of human diseases, including CsA-induced nephropathy (33), Marfan syndrome (34), skeletal myopathies (35), and transgenic overexpression of a cardiac troponin T mutation (36). To assess the effects of losartan in HCM, we treated prehypertrophic α-MHC 719/+ mice for 2 weeks prior to and during CsA induction of HCM.…”
Section: Proliferation and Characterization Of Activated Non-myocyte mentioning
confidence: 99%
“…Recent data demonstrate that angiotensin II promotes cardiac fibrosis in part by activating Tgf-β signals (32). Moreover, the angiotensin II type I receptor antagonist losartan has had salutary effects on animal models of human diseases, including CsA-induced nephropathy (33), Marfan syndrome (34), skeletal myopathies (35), and transgenic overexpression of a cardiac troponin T mutation (36). To assess the effects of losartan in HCM, we treated prehypertrophic α-MHC 719/+ mice for 2 weeks prior to and during CsA induction of HCM.…”
Section: Proliferation and Characterization Of Activated Non-myocyte mentioning
confidence: 99%
“…In animal models, SCD in transgenic mice with HF is correlated to high myocardial fibrosis (collagen) content [35,36]. Furthermore, blockade of the angiotensin II receptor type 1 by losartan has been shown to reverse and attenuate myocardial fibrosis in a transgenic HF model [37]. Taken together, the clinical and animal studies indicate that activation of the RAAS plays a critical role not only in promoting myocardial fibrosis, but also confers increased risk for SCD in HF patients.…”
Section: Renin-angiotensin-aldosterone (Raas) Cascadementioning
confidence: 99%
“…83 Previous studies have suggested that losartan reduces TGF-␤ expression in heart and kidney. 84,85 Mdx mice treated for 6 to 9 months with losartan demonstrated less fiber size heterogeneity, less fibrosis per area, and increased strength by grip strength and absolute force of explanted muscle. 83 Many older DMD patients are currently being treated with losartan for the presumptive cardiac benefits of angiotensin II-type 1 receptor blockers, as previously described.…”
Section: Modulation Of Muscle Growth and Regenerationmentioning
confidence: 94%